Caregiver training: Evidence of its effectiveness for cognitive and functional improvement in older adults. Issue 5 (24th March 2022) - Sanjuán, Miriam; Navarro, Elena; Calero, María Dolores
Abstract: Aims and objectives: The objectives of this study were to assess the benefits of a caregiver training programme on the cognitive and functional status of older adults, and to compare the effects of this programme according to type of caregiver (professional vs. family caregiver). Background: Due to demographic changes that have resulted in an aging population, the role of caregiver of an older adult has become very important in recent years. Design and Methods: The sample was composed of 160 older adults: (a) 100 received care from caregivers who had taken the three‐month training programme (treatment group), of which 60 were professional caregivers and 40 were family caregivers, and (b) 60 received care from caregivers who had not taken the programme (control group). In order to evaluate programme effects on cognitive and functional status, we used both direct measures answered by the older adults (MMSE, CAPE and EuroQol) and caregiver reports (Barthel and RMPBC). We used a quasi‐experimental, pre‐post design. We followed SQUIRE 2.0 guidelines for reporting. Results: The results showed that older adults who were cared for by caregivers that had participated in the training programme showed gains in quality of life and cognitive ability and maintenance of functional ability. Within the treatment group, although everyone significantly improved their scores, the older adults cared for by family caregivers improved in more of the cognitive sub‐items than did their peers in the professional caregiver group. Conclusions: The data obtained show that a caregiver training programme based on cognitive stimulation produces cognitive, functional and health‐related quality‐of‐life benefits in older adults. Furthermore, the caregivers reported increased satisfaction with their work. Relevance to clinical practice: The improvements obtained in the older adults and in caregivers show the relevance of this type of intervention when working in the clinical field of caregiving.